The effect of global geopolitical risk and world oil prices on abnormal stock returns in the energy sector, with global market volatility as a moderating variable - Safira Azzahra; Lestari Wuryanti; Harold Kevin Alfredo (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of global geopolitical risks and world oil prices on abnormal returns of energy sector stocks with global market volatility as a moderation variable. The study uses a quantitative approach with secondary data from energy sector companies listed on the Indonesia Stock Exchange, where global geopolitical risk is measured using the Geopolitical Risk index (GPR), world oil prices are represented by international crude oil prices, global market volatility is proxied by the VIX index, and abnormal returns are calculated using market models. The analysis method used was panel data regression with an interaction model. The results of the study show that global geopolitical risks do not have a significant effect on abnormal returns of energy sector stocks, while world oil prices have a negative and significant effect on abnormal returns of energy sector stocks, which indicates that the increase in world oil prices is responded negatively by the market. In addition, global market volatility is unable to moderate the relationship between global geopolitical risks and world oil prices to abnormal returns in energy sector stocks, thus showing that the dynamics of world oil prices are more dominant in influencing abnormal returns than other global external factors in the Indonesian capital market.